(untitled) (Lantanida Journal, 2017)
Degradation of Methanil yellow has been done. In this research the degradation process was done by sunlighting and using TiO2-SnO2 catalysis. The residu of methanil yellow was centrifuged and measured by UV/Vis Spectrophotometer at 300 – 600 nm after degradation. 6 mg/L of Methanil yellow and addition of 0,03 g TiO2-SnO2 for 150 min, gave the percentage of degradation 98,413% after lighted by sun with 1,13256 1015 foton cm-2/s intensity.